Age- and Sex-Specific Morphologic Variations of Capital Femoral Epiphysis Growth in Children and Adolescents Without Hip Disorders. Issue 6 (21st June 2018) - Novais, Eduardo N.; Maranho, Daniel A.; Kim, Young-Jo; Kiapour, Ata
Background: Understanding the development of the capital femoral epiphysis is essential to identify pathologic variations that may lead to cam morphology. Purpose/Hypothesis: The purpose of this study was to investigate the development of the capital femoral epiphysis during childhood and adolescence, with specific morphologic analysis of the peripheral growth and the metaphyseal surface of the growth plate. We hypothesized that age- and sex-dependent morphologic variations of the peripheral growth (cupping) and surface anatomy (epiphyseal tubercle) of the epiphysis would be evident with increasing age. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Pelvic computed tomography scans of 80 children and adolescents (range, 8-15 years; n = 10 per age group; 50% male), imaged because of suspected appendicitis, were used to reformat the proximal femur. All patients had asymptomatic hips with no signs or history of hip disorder. We measured the peripheral cupping of the epiphysis and the epiphyseal tubercle dimensions from 3-dimensional models. All measurements were normalized to the epiphyseal diameter. The effect of age on these parameters was evaluated by use of linear regression analysis. A 2-way analysis of variance (ANOVA) was used to compare these parameters between males and females. Results: The mean epiphyseal cupping increased with increasing age ( R 2 = 0.54; P < .001). The mean normalized epiphyseal cupping was consistently higher in the anterior and posterior directions compared with the inferior and superior locations. Male patients aged 10 and 11 years had lower ( P = .002) mean epiphyseal cupping compared with female patients of the same age. We observed no difference between male and female participants after 12 years of age ( P > .3). The normalized epiphyseal tubercle height ( R 2 = 0.08; P = .009), width ( R 2 = 0.13; P = .001), and length ( R 2 = 0.45; P < .001) decreased with increasing age, with no differences between male and female patients. On average, a 2.6-fold increase was found in epiphyseal cupping from 8 to 15 years of age, whereas normalized tubercle height decreased by 0.4-fold. Conclusion: Peripheral cupping of the epiphysis over the metaphysis increases with age, while the relative epiphyseal tubercle dimensions decrease. Females have an earlier onset of rapid increase in the peripheral cupping compared with males; however, no differences in epiphyseal tubercle dimensions were found between male and female patients. These findings may guide future studies investigating the development of cam morphology, which should consider the surface morphologic characteristics of the capital femoral epiphysis, the growth plate, and the differences in morphologic characteristics according to age and sex.